ҚАЗАҚСТАНДАҒЫ ТОҚЫМА ЖƏНЕ ТІГІН ӨНЕРКƏСІБІ КƏСІПОРЫНДАРЫНЫҢ ДАМУ ТЕНДЕНЦИЯСЫН ТАЛДАУ (Journal of Economic Research & Business Administration, 2015)
In this article, author analyzes the trends in textile and clothing industry in Kazakhstan and considers the main trends in this sphere.